Characteristics and outcomes of surgically ineligible patients with multivessel disease treated with percutaneous coronary intervention. Issue 7 (3rd February 2021) - Shields, Mary C.; Ouellette, Michelle; Kiefer, Nicholas; Kohan, Luke; Taylor, Angela M.; Ailawadi, Gorav; Ragosta, Michael
Abstract: Objectives: In this study we evaluated the clinical characteristics and outcomes of surgically ineligible patients with coronary artery disease (CAD) who underwent multivessel percutaneous coronary intervention (PCI). Background: Patients with multivessel CAD who are surgically ineligible and undergo PCI are not well represented in large trials. Methods: Out of 1, 061 consecutive patients who underwent a non‐emergent PCI for unprotected left main or multivessel CAD at the University of Virginia Medical Center, 137 patients were determined to be surgically ineligible for coronary artery bypass graft (CABG) surgery by a heart team. The clinical characteristics and reasons for surgical ineligibility were collected. The coronary angiograms were reviewed and the SYNTAX score calculated. The Society of Thoracic Surgeons (STS) score was calculated. Outcomes were determined at 30 days and 1‐year. Results: The mean age of the cohort was 71 and 59% were women. Hypertension, hyperlipidemia, tobacco abuse, and diabetes were common comorbidities. The average SYNTAX score was 22. The most commonly cited reasons for surgical ineligibility were advanced age, frailty, severe lung disease, ejection fraction ≤ 30% and STS score ≥ 8%. Outcomes at 30 days were excellent and better than those predicted by STS for surgery. Frailty and STS score predicted one‐year outcomes. Conclusions: Patients undergoing PCI for multivessel disease who are surgically ineligible have multiple risk factors and comorbidities. Frailty, lung disease, poor left ventricular function, and high STS score represent common reasons for surgical ineligibility. Frailty and the STS score better predict one‐year outcomes after PCI compared to the SYNTAX score.